The Influence of Teachers’ Teaching Styles and Social Support on Self-Efficacy and Learning Motivation Among 11th-Grade Students at SMK Negeri 44 Jakarta - Destria Amara; Dita Puruwita; Rizka Zakiah (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to analyze the influence of teachers’ teaching styles and social support on the self-efficacy and learning motivation of 11th-grade students at SMK Negeri 44 Jakarta. The method used was a quantitative approach with a population of 210 students; the research sample consisted of 136 students. Data collection was conducted via an online questionnaire using Google Forms. Data processing and analysis were performed using Partial Least Squares (PLS)-based Structural Equation Modeling (SEM) with SmartPLS 4.0 software. The results of the outer model test showed that all indicators met the criteria for convergent validity, discriminant validity (HTMT < 0.85), and reliability, with composite reliability and Cronbach’s alpha values above 0.70. Meanwhile, the inner model evaluation yielded an R-Square value of 0.413 for the self-efficacy variable and 0.457 for the learning motivation variable. Hypothesis testing showed that teaching style (β = 0.397; t-value = 3.908; p-value = 0.000) and social support (β = 0.318; t-value = 3.069; p-value = 0.002) had a positive and significant effect on self-efficacy. In addition, social support (β = 0.367; t-value = 3.040; p-value = 0.002) and self-efficacy (β = 0.281; t-value = 2.295; p-value = 0.022) had positive and significant effects on learning motivation. Conversely, the teacher’s teaching style did not have a significant effect on learning motivation (β = 0.151; t-value = 1.311; p-value = 0.190). The implications of this study indicate that students have high confidence in achieving their learning goals; future aspirations are the primary factor driving learning motivation; teachers are the source of social support most felt by students; and teachers’ nonverbal communication has supported the creation of engaging learning experiences, although the pace of speech still needs improvement.